SYNCHRONIZATION IN DIGITAL SYSTEM DESIGN - YADAV, RONIT; SOLANKI, SACHIN; ARORA, SAHIB (IJRDO -Journal of Computer Science Engineering, 2015)
In digital system design, the methods of synchronous & asynchronous designing have their own merits and de-merits. Designers adopt the appropriate method based on the requirements like power efficiency, modularity, performance, clock skew, concurrency, metastability, testability, design tools support, automatic adaptation to physical properties and many more. The “need for testability” is the driving factor to select the method of synchronous design. This helps to achieve comparatively better testability than the design based on asynchronous design. The synchronous design method was applied for a bus control unit to control heater switches from both the serial and I/O ports.